Cucumber Mosaic Virus and Chili Veinal Mottle Virus Infection on Growth and Yield Component of Chilli - DWI SUBEKTI; SRI HENDRASTUTI HIDAYAT; ENDANG NURHAYATI; SRIANI SUJIPRIHATI (HAYATI Journal of Biosciences, 2006)
A research was undergone to study the effect of single and double infection of Cucumber Mosaic Virus (CMV) and Chili Veinal Mottle Virus (ChiVMV) on the growth and yield of five chilli cultivars, i.e. Prabu, Taro, Jatilaba, Laris, and Keriting Bogor. Mechanical inoculation was conducted to transmit the virus. Infection of the virus was then confirmed with DAS-ELISA. Severe symptom was observed on plant given double infection compared to those given single infection. The rate of plant growth and the amount and weight of fruits were reduced. The type of interaction between CMV and ChiVMV on most chilli cultivar can be considered as interference and additive. Synergism interaction was only observed on cultivar Laris. Based on symptom expression and reduction on yield, it can be concluded that all chilli cultivars used in this study could not hold up the virus infection. Key words: CMV, ChiVMV, interaction, additive, interference, synergism